Suatu Refleksi Teologis: Memaknai Karya Seni Catacomb Dan Implikasi Bagi Pembinaan Warga Gereja - Halawa, Angilata Kebenaran; Setiawan, David Eko; Tahya, Alton Perejon; Sitanala, Andhy Readhy (Sekolah Tinggi Teologi Kharisma, 2021)
The congregation in a church needs formation. Community Development of the Church is an effort or act of organizing church members, to equip and train members of the congregation so that their faith in Jesus Christ grows. the church needs to nurture the congregation to grow in Christ through various forms. Like the early Christians, they inspired themselves through a painting in a Catacomb or a hallway that was used as a place for the dead. They inspire themselves through the paintings in one of the early Christian collections, namely the sacrament cubicle. Paintings of Jonah, Jesus and Samaria, Jesus the Good Shepherd and so on. Thus, this model can be used as a suggestion for the formation of church members through paintings that inspire and strengthen faith. Jemaat dalam sebuh gereja membutuhkan pembinaan. Pembinaan Warga Gereja ialah suatu usaha atau tindakan pengorganisasian warga gereja, untuk melengkapi dan melatih warga jemaat agar iman kepada Yesus Kristus bertumbuh. gereja perlu membina jemaat agar semakin bertumbuh di dalam Kristus melalui berbagai bentuk. Seperti halnya, orang Kristen mula-mula, mereka menginspirasi diri mereka melalui lukisan didalam Catacomb atau sebuah Lorong yang dijadikan sebagai tempat orang yang sudah meninggal. Mereka menginspirasi diri mereka melalui lukisan-lukisan yang ada di dalam salah satu koleksi Kristen mula-mula, yaitu kubikula sakramen. Lukisan mengenai Yunus, Yesus dan Samaria, Yesus Gembala yang baik dan sebagainya. Dengan demikian, model ini dapat dijadikan saran untuk pembinaan warga gereja melalui luksian-lukisan yang menginspirasi dan menguatkan iman.